REPRESENTATIONS OF CULTURAL CONFLICT IN JHUMPA LAHIRI’S THE NAMESAKE - Neha (International Journal of Research -GRANTHAALAYAH, 2026)
Jhumpa Lahiri’s The Namesake presents an intimate portrait of a Bengali family attempting to build a life in the United States while carrying the emotional weight of their past. The novel explores questions of cultural belonging, displacement, memory, and family expectations through clear and graceful storytelling. Themes such as nostalgia, loss, and longing shape the experiences of characters who migrate in search of opportunity yet remain tied to their origins. The narrative captures the quiet tensions of living between two cultural worlds and offers a close study of how a small family negotiates this journey across borders. This study examines the first and second generation immigrant characters in the novel to understand how cultural conflict and identity struggles emerge within the framework of contemporary cultural thought. It also considers how the attraction of American life interacts with the persistent pull of inherited traditions, and how relationships formed in a foreign land are continually influenced by values carried from the past.